Role of public and private funding in the rising caesarean section rate: A cohort study - Einarsdóttir, K.; Haggar, F.; Pereira, Gavin; Leonard, H.; De Klerk, N.; Stanley, F.; Stock, S. (2013)
Objective: The caesarean section rates have been rising in the developed world for over two decades. This study assessed the involvement of the public and private health sectors in this increase. Design: Population-based, retrospective cohort study. Setting: Public and private hospitals in Western Australia. Participants: Included in this study were 155 646 births to nulliparous women during 1996-2008. Main outcome measures: Caesarean section rates were calculated separately for four patient type groups defined according to mothers' funding source at the time of birth (public/private) and type of delivery hospital ( public/private). The average annual per cent change (AAPC) for the caesarean section rates was calculated using joinpoint regression. Results: Overall, there were 45 903 caesarean sections performed (29%) during the study period, 24 803 in-labour and 21 100 prelabour. Until 2005, the rate of caesarean deliveries increased most rapidly on average annually for private patients delivering in private hospitals (AAPC=6.5%) compared with public patients in public hospitals (AAPC=4.3%, p<0.0001). This increase could mostly be attributed to an increase in prelabour caesarean deliveries for this group of women and could not be explained by an increase in breech deliveries, placenta praevia or multiple pregnancies. Conclusions: Our results indicate that an increase in the prelabour caesarean delivery rate for private patients in private hospitals has been driving the increase in the caesarean section rate for nulliparous women since 1996. Future research with more detailed information on indication for the prelabour caesarean section is needed to understand the reasons for these findings.